(untitled) (Mustansiria Dental Journal, 2024)
This in vitro study was conducted to evaluate the effect of different surface treatment (sandblasting with 50µm of Al2O3, etching with 5% of hydrofluoric acid and a combination of 50 µm of Al2O3and 5% of hydrofluoric acid) on the shear bond strength of veneering ceramic to zirconia and e.max press substructures . Eighty rectangular specimens (9mm length ×4mm width×4mm height) were fabricated and divided into two major groups(zirconia and e.max press), Forty specimens for each group. Then, each group was subdivided into four subgroups according to surface treatment (control group, sandblasting by 50µm of Al2O3,etching with 5% of hydrofluoric acid and a combination of 50 µm of Al2O3 and 5% of hydrofluoric acid),10samples for each group. then, they veneered with their corresponding veneering ceramic material (Vita VM9 ,E.max ceram) according to manufacturer’s instructions. The results of shear bond strength test revealed that the highest mean was for a combination treatment groups followed by sandblasting groups then etching with acid groups and finally untreated groups. One-way ANOVA test showed there is highly significant difference among each subgroups. While, LSD test for zirconia subgroups showed, there is no-significant difference between acid etching (ZHF) and untreated (ZC) groups. Also, LSD test for e.max press subgroups showed there was non-significant difference between acid etching (EHF) and sandblasting (ESB) groups. student’s t-test between two major groups showed, higher significant difference among untreated groups and sandblasting groups. While, there was significant difference among acid etching groups and a combination treatment groups for each major group. A combination of two surface treatments represented an effective method on the bond strength due to the cumulative effect of these treatments